Commentary: Making the brain matter in assessing and treating adolescent substance use – a commentary on Conrod and Nikolaou (2016). (March 2016) - Mosconi, Matthew W.; Lejuez, Carl W.
Abstract : Adolescence represents a period of vulnerability to psychiatric problems due to a range of factors, including advances in social and cognitive abilities, increased levels of autonomy in decision‐making and behavioral governance, and greater exposure to opportunities for risk‐taking behavior. Adding to these psychological and social challenges, adolescence also is marked by robust maturational changes affecting both the microcircuitry and connectivity between widely distributed brain systems. These changes alter the communication among parallel, distributed brain networks, have implications for one's vulnerability to engage in risk behavior and make the brain particularly susceptible to external perturbations, such as exposure to neurotoxic substances. Abstract : Read the full article at doi:10.1111/jcpp.12516